Although Anatomically Micrometers Apart: Human Periodontal Ligament Cells Are Slightly More Active in Bone Remodeling Than Alveolar Bone Derived Cells - Loo-Kirana, Rebecca; Gilijamse, Marjolijn; Hogervorst, Jolanda; Schoenmaker, Ton; de Vries, Teun J. (Frontiers in Cell and Developmental Biology, 2021)
Abstract The periodontal ligament (PDL) and the alveolar bone are part of the periodontium, a complex structure that supports the teeth. The alveolar bone is continuously remodeled and is greatly affected by several complex oral events, like tooth extraction, orthodontic movement and periodontitis. Until now, the role of PDL cells in terms of osteogenesis and osteoclastogenesis has been widely studied, whereas surprisingly little is known about the bone remodeling capacity of alveolar bone. Therefore, the purpose of this study was to compare the biological character of human alveolar bone cells and periodontal ligament cells in terms of osteogenesis and osteoclastogenesis in vitro. Paired samples of PDL cells and alveolar bone cells from 7 patients with compromised general and oral health were collected and cultured. Bone A (early outgrowth) and bone B (late outgrowth) were included. PDL, bone A, bone B cell cultures all had a fibroblast appearance with similar expression pattern of 6 mesenchymal markers. These cultures were subjected to osteogenesis and osteoclastogenesis assays. For osteoclastogenesis assays, the cells were co-cultured with peripheral blood mononuclear cells, a source for osteoclast precursor cells. The total duration of the experiments was 21 days. Osteogenesis was slightly favored for PDL compared to bone A and B as shown by stronger Alizarin red staining and higher expression of RUNX2 and Collagen I at day 7 and for ALP at day 21. PDL induced approximately two times more osteoclasts than alveolar bone cells. In line with these findings was the higher expression of cell fusion marker DC-STAMP in PDL-PBMC co-cultures compared to bone B at day 21. In conclusion, alveolar bone contains remodeling activity, but at a different extent compared to PDL cells. We showed that human alveolar bone cells can be used as an in vitro model to study bone remodeling.